Replenishment of intracellular magnesium deficiency in cardiac arrhythmias: focus on the physicochemical properties of complex compounds - Ya. G. Bozhko; N. A. Belokonova; O. M. Medvedeva; K. A. Butova; M. V. Arkhipov (Рациональная фармакотерапия в кардиологии, 2025)
Aim. To identify the most promising drug composition for replenishing intracellular magnesium deficiency by eveluating the physicochemical properties of magnesium complex compounds and conducting experiments on isolated rat atrial cardiomyocytes.Materials and methods. The study assessed the osmolality of solutions containing magnesium complex compounds, their extraction into organic solvents of different polarity (chloroform and butanol), and diffusion through a cell membrane model (lecithin-modified paper filter). In experiments on isolated rat atrial cardiomyocytes, the compositions were tested for replenishment of intracellular (cytosolic) magnesium deficiency using laser scanning (confocal) microscopy.Results. Based on physicochemical testing of magnesium preparations and experiments conducted on cardiomyocytes of laboratory animals, the most promising system for replenishing intracellular magnesium was a system based on magnesium aspartate, in which the ratio of magnesium ions to aspartic acid is 1 to 2.5. Thirty-minute incubation with this preparation led to increased cytosolic [Mg2+]i by 115% compared to control. Removal of excess potassium ions from the potassium aspartate and magnesium system shifted pH toward a more physiological range (from 6.8 to 7.3), while the lipophilic properties (organic solvent extraction and lecithin filter diffusion) doubled.Conclusion. The paper presents a methodological approach for analyzing of magnesium complex compounds for replenishing its intracellular deficiency, emphasizing complex type, concentration, lipophilicity, and original system osmolality. Experimental findings were confirmed in a translational experiment with isolated atrial cardiomyocytes, which allows us to identify the most promising complex in relation to replenishing intracellular magnesium deficiency.